Enhancement of Plasmonic Performance in Epitaxial Silver at Low Temperature - Liuyang Sun (Nature Portfolio, 2017)
Abstract We report longer surface plasmon polariton propagation distance based on crystalline crystal silver at low temperature. Although enhanced plasmonic performance at low temperature has been predicted for a long time, it has not been directly observed on polycrystalline silver films which suffer from significant plasmonic losses due to grain boundaries and rough silver surface. Here we show that longer propagation distance can be achieved with epitaxial silver at low temperature. Importantly, the enhancement at low temperature are consistent across silver films grown with different methods.